Evaluation of a Pharmacist Led Oral Chemotherapy Clinic: A Pilot Program in the Gastrointestinal Oncology Clinic at an Academic Medical Center - Julianne O. Darling; Farah Raheem; Katelyn C. Carter; Elizabeth Ledbetter; Jennifer F. Lowe; Christopher Lowe (MDPI AG, 2020)
Oral chemotherapy represents a major patient-centric advancement in therapy convenience. However, ownership of safe and correct administration of these agents requires significant patient education. To address this challenge, an in-person pharmacist-led oral chemotherapy education clinic in gastrointestinal oncology patients within an academic medical center was created and assessed. In this pilot program, a medication-specific quiz was administered to patients before and after education performed by a pharmacist to assess patient understanding of their new oral chemotherapy. A five-question satisfaction survey was also administered at the conclusion of the pharmacist clinic visit. Primary outcome was the percentage difference between pre-and post-education quiz scores. Secondary outcomes included patient satisfaction, time to treatment initiation, and number of pharmacist interventions. Frequencies and medians were used to describe categorical and continuous variables, respectively. Of the 18 patients analyzed, 50% were male and median age was 59.5 years. Approximately 28% had colon cancer, and 61% were treated with capecitabine. The median post-education scores improved from a pre-education score of 75% to 100%. Overall, seventeen of the eighteen patients responded with “strongly agree” to all satisfaction survey statements. An in-person oncology pharmacist-led oral chemotherapy education session demonstrated an improvement in patients’ understanding of their new oral chemotherapy treatment.